China and Central Asian Regional Reconstruction: “One Belt One Route (International Journal of Emerging Trends in Science and Technology, 2017)
The Chinese Silk Road is the Trans-Eurasian network of trade routes connecting East and Southeast Asiato Central Asia, India, Southwest Asia, Mediterranean, and Northern Europe. The Road flourishedroughly from 100 BC to around 1450.The Road is a system of caravan roads that in Ancient Timesand Middle Ages traversed Eurasia from Mediterranean to China. From historic times it flourished thedevelopment of trade and cultural relations between peoples and actors involved. The Silk Road actsas a symbol of openness, inclusiveness, cooperation and peace. It also acts as a place where the humanist,spiritual, cultural, artistic and technical exchanges take place. The One Belt and One Road program is amajor strategic measures introduced by China in response to the emerging trends in EconomicGlobalization. China proposes a new approach of promoting worldwide economic prosperity and tobenefiting other regions in terms of driving forward cross-regional economic integration througheconomic growth in China and Asia. In the Post Cold War Period, there are at least two reconstruction thatare historically very significant in Eurasian continent, one is the implosion of Soviet Union, the other willbe the “Belt and Road” initiative in China.In this context the present study wants to explore the new project of Silk Route, challenges and prospectsthat china is facing in building its project. It is thus significant in analyzing the impact of the project toreconstruct regional interests and balance powers throughout the world especially Central Asia. The studywill also focus on the following questions as what are the future prospects, will the neighbouring countriesbenefit from the initiative? And will China‟s investment enrich the world?